Hubungan kebiasaan belajar dengan prestasi belajar siswa sekolah menengah atas Pertiwi 1 Padang - Andriani, Riska (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
ThisÂ  research background is the low students achievement achievement at school. Study habits are factors suspected influence students academic achievement. This research was intended to describe: (1) the study habits and students academic achievement, (2) the relationship of study habits with students academic achievement. This research used quantitative method by using descriptive correlational. The population in this research are class X and XI students of High School of Pertiwi 1 Padang which are 621 students.Â  The samples are 243 students which are taken through the stratified random sampling. The instrument are used in the scale Likert. The data analyzed using descriptive statistics. The findings of this research showed that: (1) in average the study habits of students that are in good enough category and students academic achievement are in good enough, (2) there is a relationship significant between study habits with students academic achievement.